2016
DOI: 10.1371/journal.pone.0158038
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Irisin on Atherosclerosis via Suppressing Oxidized Low Density Lipoprotein Induced Vascular Inflammation and Endothelial Dysfunction

Abstract: Irisin, a newly discovered myokine, is considered as a promising candidate for the treatment of metabolic disturbances and cardiovascular diseases. In the present study, we used two animal models, apolipoprotein E-deficient mice fed on a high-cholesterol diet and a mouse carotid partial ligation model to test the anti-atherosclerotic effect of irisin. Irisin treatment (0.5 μg/g body weight/day) significantly reduced the severity of aortic atherosclerosis in apolipoprotein E-deficient mice fed on a high-cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 45 publications
2
83
0
1
Order By: Relevance
“…It has been suggested that irisin seems to be beneficial for many metabolic diseases including diabetes and obesity through promoting the browning of white adipocytes [25]. Recent studies demonstrated that altered irisin levels are related to endothelial function [26, 27]. Irisin improves endothelial function and atherosclerosis in diabetic mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that irisin seems to be beneficial for many metabolic diseases including diabetes and obesity through promoting the browning of white adipocytes [25]. Recent studies demonstrated that altered irisin levels are related to endothelial function [26, 27]. Irisin improves endothelial function and atherosclerosis in diabetic mice [27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, abundant data have shown that the initiation and propagation of endothelial cell (EC) dysfunction in the coronary artery are the fundamental mechanism for the development of arteriosclerosis, followed by plaque formation and ultimately, plaque fissuring and rupture, resulting in acute obstructive syndrome . A large number of studies have reported that inflammation, generations of oxidative stress/free radicals, and oxidized low‐density lipoprotein (LDL) as well as aging are crucial contributors to the initiation and propagation of EC dysfunction . Thus, early interventions (ie, primary prevention) using health supplements to prevent and alleviate endothelial dysfunction may be a feasible approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the mechanisms through which the heart benefits from physical activities through the increase of irisin levels might be the major role irisin plays in maintaining the functioning of endothelial cells. Irisin has thus been known as a potential medicinal aid in treating atherosclerosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, regular physical exercise is proportionate to atherosclerosis and the occurrence of primary and secondary cardiovascular attacks, although the mechanisms of physical exercise leading to prevention of atherosclerosis are not clearly known yet (18). Nonetheless, these are perhaps, a combination of optimal energy balance, fatness limitation and inflation, which is the potential result of the secretion of myokines (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation